KONSTRUKSI MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS MASYARAKAT DALAM PENINGKATAN MUTU PENDIDIKAN POS PAUD II BASEH KEDUNGBANTENG BANYUMAS - Lilis Suryatini; Muhammad Nurhalim (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Early childhood education (PAUD) aims to develop all children's potential so that in the future they can function as complete human beings according to the culture, tradition and philosophy of a nation. POS PAUD II Baseh is an institution prepared to provide quality human resources. Quality human resources will improve the quality of a country. Therefore, efforts to improve the quality of human resources cannot be separated from education. The research method used is qualitative with a descriptive approach. Community participation in education financing at POS PAUD II Baseh is carried out by involving the community in decision making regarding the preparation of expenditure budget plans based on deliberation to reach consensus through the stages of problem analysis, potential analysis and analysis of community interests, both in the type of capital cost and recurrent cost financing in where the form of participation is carried out through attendance at student guardian meetings, POS PAUD II Baseh building construction committee meetings, and other meetings in the POS PAUD II Baseh area, community participation in implementation